USAGE OF METHOD OF SITUATIONAL STUDYING IN TEACHING THE COURSE OF PROFESSIONAL FOREIGN LANGUAGE - Старинець, Олена Анатоліївна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The article gives the analysis of justification and ways of usage of method of situational studying in teaching the course «Professional foreign language», various types of activities and principles of choosing the materials are given. It is determined that the development of communicative competence occurs in accordance with the ability of students to learn, their knowledge of the subject and their previous experience and it’s performed within the limits of situational context connected with teaching and specialization. The article gives grounds for the revision of teaching methods with the consideration of communicative-situational approach